DECISION MAKING IN POLICY LEARNING MODEL THROUGH STUDENT MATHEMATICS REPRESENTATION ABILITY TEST IN LEARNING TWO VARIABLE LINEAR EQUATIONS - Ira Yoshita Cahyaningrum; Surya Sari Faradiba (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
This study aims to make decisions about learning model policies by exploring students' mathematical representations in learning mathematics. The benefit of the ability to represent mathematics is that it facilitates problem-solving. Students need to train and develop things related to mathematical representation in a lesson. The form of mathematical representation used is a visual representation, making mathematical models, and using words in problem-solving. From the results of the study, it was found that the students' mathematical representation skills were linear equations of two variables, namely students as the first subject in the very capable category of students fulfilling complete and very good mathematical representations. Students with moderate academic ability in the second subject and meeting the mathematical representation ability were quite good, while students in the third subject with existing indicators had incomplete results and did not meet the mathematical representation.